PENGARUH PERLAKUAN PADA KLOBOT JAGUNG SEBAGAI KEMASAN TERHADAP MUTU KERAKE SELAMA PENYIMPANAN - Desy Ambar Sari; Zainuri Zainuri; Wiharyani Werdiningsih (Universitas Muhammadiyah Malang, 2021)
The aim of this research was to determine the effect of pre-treatment on corn husks as primary packaging for kerake quality during storage. The design used in this research was Completely Randomized Design (CRD) with a single factor i.e. pretreatment consisted of K1 (drying), K2 (combination of steaming and drying), K3 (heating with irons), K4 (sterilization by autoclave), and K5 (oven) and it was repeated three times. Data were analyzed using Co-Stat software with 5% significance differences. The treatments that were significantly different were then analyzed using Honestly Significance Difference (HSD). The results showed that pretreatment of the corn husks as primary packaging was not significantly different on moisture content, fat content, taste, and texture kerake during storage. But were significantly different on flavor kerake. Steaming and drying treatment was able to decrease the growth of total fungi to <1.0 x 102 CFU/gr during 14 days of storage, which means total fungi were still accepted according to SNI (maximum 1.0 x 102 CFU/gr). Steaming and drying treatment also produced kerake with flavor, texture, and aroma that is preferred by panelists.